Sex ratio and women's career choice does a scarcity of men lead women to choose briefcase over baby? [article]. - Durante, Kristina M.
Although the ratio of males to females in a population is known to influence behavior in nonhuman animals, little is known about how sex ratio influences human behavior. We propose that sex ratio affects women's family planning and career choices. Using both historical data and experiments, we examined how sex ratio influences women's career aspirations. Findings showed that a scarcity of men led women to seek high paying careers and to delay starting a family. This effect was driven by how sex ratio altered the mating market, not just the job market. Sex ratios involving a scarcity of men led women seek lucrative careers because of the difficulty women have in finding an investing, long-term mate under such circumstances. Accordingly, this low-male sex ratio produced the strongest desire for lucrative careers in women who are least able to secure a mate. These findings demonstrate that sex ratio has far-reaching effects in humans, including whether omen choose briefcase over baby. - (from the authors)